Efficient Purification of Auto-Exhaust Soot Particles Using Hexagonal Fe2O3 Nanosheets Decorated with Non-Noble Metals (Ni) - Haoqi Guo; Jing Xiong; Peng Zhang; Jian Liu; Zhen Zhao; Yuechang Wei (Nanomaterials)
Purification of soot particles from automobile exhaust has closely to do with the synergistic effect between catalyst metals. Here, several binary Ni-Fe oxide catalysts were elaborately prepared via a modified solvothermal method. A non-noble-metal (Ni)-modified hexagonal Fe2O3 nano-sheet catalyst (Ni−Fe2O3) was prepared. The introduced heteroatoms replace some of the Fe atoms, which take up the surface of the [FeO6] octahedron, and the synergistic effect formed between the heteroatoms which are on the surface and the adjacent Fe atoms promotes the formation of coordination unsaturated ions of the activated reactants. The optimal performance was obtained with the Ni-Fe2O3-20 composition, with catalytic soot oxidation resulting in T50, SCO2m, Ea and TOF of 366 °C, 99.1%, 72.7 kJ mol−1 and 0.156 min−1 (at 310 °C), respectively. The combination of Ni and Fe2O3 cells increases the ratio of Fe3+/Fe2+, making the interaction among electrons between the Ni, which was proved highly dispersed over the catalyst, and the Fe2O3 strong. Both exist on the catalyst surface in the form of NiFe2O4. Ni atoms and Fe2O3, which demonstrate a synergistic effect, promoting the formation of coordination unsaturated ions of the activated reactants and generating more oxygen vacancies, thus promoting the adsorption of NO and accelerating the ignition of soot in O2 at a low temperature. The novel Ni-Fe2O3-X oxide cocatalyst is an improved noble-free catalyst that promotes the synergistic effect between heteroatoms and metal oxides through surface regulation. This is of great significance for the further development of economic and efficient catalysts for soot particle removal from automobile exhaust.